2017
DOI: 10.5740/jaoacint.16-0201
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Capillary Electrophoretic Method for the Determination of Olopatadine and Its Application to a Pharmaceutical Preparation of Eye Drops

Abstract: A validated rapid and sensitive capillary zone electrophoretic method for the determination of olopatadine hydrochloride (OLO) is described. Optimum conditions were found: 20 mmol/L sodium tetraborate buffer, acetonitrile 15% (v/v), 10 mmol/L NaCl at pH 9.5, with 25 kV of applied potential, injection time of 10 s at 5 × 103 N/m2, at a wavelength of 205 nm, and fixed temperature of 30°C. The calibration curve was linear in the range of 1.13 × 10-5 mol/L (4.22 μg/mL) to 5.65 × 10-5 mol/L (21.12 μg/mL), with R = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this method the standard and sample solutions of olopatadine hydrochloride were prepared in methanol. Olopatadine hydrochloride was estimated at 224 nm for the second order derivative UV -spectrophotomet-formed [15]. The validated capillary zone electrophoretic method for the determination of olopatadine hydrochloride is described at pH 9.5, with 25 kV.…”
Section: Methods Of Determinationmentioning
confidence: 99%
“…In this method the standard and sample solutions of olopatadine hydrochloride were prepared in methanol. Olopatadine hydrochloride was estimated at 224 nm for the second order derivative UV -spectrophotomet-formed [15]. The validated capillary zone electrophoretic method for the determination of olopatadine hydrochloride is described at pH 9.5, with 25 kV.…”
Section: Methods Of Determinationmentioning
confidence: 99%
“…It offers numerous advantages over conventional chromatographic methods because of its unique separation mechanism, speed, higher efficiency, versatility, environmental friendliness, resources utilization, small sample amount, not requiring further purification, and permitting several kinds of buffers and additives for usage as the electrolyte. 20,21 CE has many applications in biochemistry, pharmaceutical science, 22 bioscience, 23 ion analysis, 24 food analysis, 25 and environmental science fields. 24 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Analytical methods for OLO determination in different matrices have been reported, i.e. radioimmunoassay, 10 liquid chromatography (LC) with tandem mass spectrometry, 11 LC-ESI-MS-MS, 12,13 capillary zone electrophoretic method, 14 high performance LC (HPLC), and high-performance thin-layer chromatography (HPTLC), 15 but there is no study reported on forced degradation profiling including the intrinsic stability of OLO. The objective of forced degradation is to provide guidance for the development of executing purposeful degradation experiments for pharmaceutical drug candidates.…”
Section: Introductionmentioning
confidence: 99%